Black and Grey behind White and Red: Authoritarian Potential in the Turkish and Polish Societies in the Light of Necla Kelek’s Bittersweet Homeland: A Report from the interior of Türkiye and Emilia Smechowski’s Return to Poland: Expeditions to My Homeland - Okoński, Krzysztof (Porównania, 2022)
Post-)migration literature by Polish and Turkish authors in Germany is no longer an artistic elaboration of life abroad, a view of the West from an Eastern perspective or a reflection of traumas, phobias and dreams from the old homeland. More and more frequently, writers with foreign roots refer to the German past and present. Similarly to authors of Turkish origin, Polish writers and journalists living in Germany are reporting on the country of their childhood—and that is not always a sentimental view. Ideological polarization, anti-democratic tendencies, patriarchy, religious radicalism, phantom pains and longing for the imperial past, nationalism and idealization of one’s own history, division of the country into pro-Western metropolises and a conservative province form a background for the journey through the rediscovered country of origin—in Poland and in Türkiye. Emilia Smechowski’s Return to Poland: Expeditions to my home country (2019) and the report by the German-Turkish sociologist Necla Kelek Bittersweet Home: Report from the interior of Turkey (2008) form the starting point for a comparative analysis of the authoritarian potentials in both societies.